2021
DOI: 10.1007/s40670-021-01309-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shortened Clinical Clerkships on Medical Student Performance and Clerkship Assessment

Abstract: Intro Medical schools sometimes need to adjust the length of third-year clinical clerkships. The literature surrounding the effects of shortened clerkships on student experience and performance is mixed. Methods Our medical school shortened the third year by an average of 20% per clerkship to accommodate a curricular redesign in 2018-2019. We examined test scores and measures of clinical performance as well as student experience in order to understand the impact of this change. Results Two hundred and eight st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…[7][8] In the remaining study, a reduction from 6 to 5 weeks led to slightly higher performance for the longer-clerkship group (Surgery Subject Examination scores were approximately 1 point higher on the equated percent correct scale). 9 These studies varied in how pre-existing differences between groups completing shorter and longer clerkships were taken into account. In some, differences were modeled directly using Step 1 scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8] In the remaining study, a reduction from 6 to 5 weeks led to slightly higher performance for the longer-clerkship group (Surgery Subject Examination scores were approximately 1 point higher on the equated percent correct scale). 9 These studies varied in how pre-existing differences between groups completing shorter and longer clerkships were taken into account. In some, differences were modeled directly using Step 1 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In some, differences were modeled directly using Step 1 scores. 9,11 In others, researchers tested for differences between pre-clerkship measures such as Medical College Admission Test (MCAT) scores, undergraduate grade point averages (GPAs), and Step 1 scores prior to comparing clerkship performance. 5,10 In three studies, the researchers did not statistically control for preclerkship differences, or simply noted that the two groups were similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several prior studies have concluded that longer Medicine clerkship length is associated with higher clinical subject exam scores, while other studies showed a lack of effect on the NBME score related to clerkship length [ 9 , 10 ]. The aim of the study was to determine whether shortening the IM clerkship time would affect the comprehensive NBME Medicine subject exam performance and also determine if students felt they had enough time to complete the IM clerkship requirements.…”
Section: Introductionmentioning
confidence: 99%